Nutritional considerations for gender-diverse people: a qualitative mini review - Mittertreiner, Em Jun Eng; Hunter, Abbey; Lacroix, Emilie (Frontiers in Nutrition, 2024)
Dietitians working with gender-diverse people may require different skills and knowledge than those caring for cisgender men and women, as indicated by a growing body of literature that highlights gender-diverse people's unique experiences with and relationships to nutrition and eating behaviors. To provide insight into how dietitians can best serve this population, this mini review identifies and summarizes qualitative studies that investigate gender-diverse people's lived experiences and perspectives regarding nutrition, eating disorders, and access to eating-related healthcare services. Fourteen studies examining nutrition or eating behaviors among gender-diverse samples were selected through a systematic search and screening process: 11 focused on disordered eating or eating disorders and the remaining three focused on nutritional needs, nutritional knowledge, and food insecurity. Extracted themes included: using dietary restriction to suppress secondary sex characteristics or conform to societal norms; the impact of gender-affirming care on disordered eating; negative experiences with, and beliefs about, nutrition and eating disorders healthcare services; and suggestions for clinicians. Recommendations discuss the need for increased trans literacy among clinicians, the creation of safe spaces for gender-diverse people with eating disorders, and the importance of dual competencies in eating disorders treatment and gender-affirming care.